2008
DOI: 10.1073/pnas.0805198105
|View full text |Cite
|
Sign up to set email alerts
|

Transduction of the cytoplasmic domain of CTLA-4 inhibits TcR-specific activation signals and prevents collagen-induced arthritis

Abstract: CTLA-4 (CD152) negatively regulates T cell activation signaling, and the cytoplasmic domain of CTLA-4 (ctCTLA-4) itself has the capacity to inhibit T cell activation in vitro and in vivo. In this study, the inhibitory mechanisms of the cell-permeable recombinant protein Hph-1-ctCTLA-4 on T cell activation and its ability to prevent collageninduced arthritis were analyzed. Hph-1-ctCTLA-4 prevented human and mouse T cell activation and proliferation by inhibition of T cell receptor-proximal signaling and the arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Because proteins fused to PTDs can pass through cell membranes and retain biological function, they also have the potential to modify lymphocyte function in a cell-autonomous manner. In recent studies, the cytoplasmic domain of cytotoxic T lymphocyte antigen 4 (CTLA4) fused to a PTd has been introduced into T cells and shown to specifically inhibit TCR signalling 47 , and the systemic administration of CTLA4-PTD ameliorated collagen-induced arthritis in mice 48 . Recent studies indicate that bispecific antibodies targeting CD3 and CD19 can mediate substantial antitumour effects that are presumably MHC independent in patients with lymphoma 49 , and thus the use of protein-based transduction and a related strategy, known as protein painting 50 , has significant opportunity to engineer enhanced lymphocyte functions without the risks of gene transfer approaches.…”
Section: Choosing the Toolsmentioning
confidence: 99%
“…Because proteins fused to PTDs can pass through cell membranes and retain biological function, they also have the potential to modify lymphocyte function in a cell-autonomous manner. In recent studies, the cytoplasmic domain of cytotoxic T lymphocyte antigen 4 (CTLA4) fused to a PTd has been introduced into T cells and shown to specifically inhibit TCR signalling 47 , and the systemic administration of CTLA4-PTD ameliorated collagen-induced arthritis in mice 48 . Recent studies indicate that bispecific antibodies targeting CD3 and CD19 can mediate substantial antitumour effects that are presumably MHC independent in patients with lymphoma 49 , and thus the use of protein-based transduction and a related strategy, known as protein painting 50 , has significant opportunity to engineer enhanced lymphocyte functions without the risks of gene transfer approaches.…”
Section: Choosing the Toolsmentioning
confidence: 99%
“…The fact that these control mechanisms sometimes fail means that the immune system in most individuals retains the capacity for re-regulation. Accordingly, experimental studies, mainly in rodent models of autoimmune disease, have revealed several different ways whereby autoimmunity can be manipulated to prevent or cure autoimmune disease 13…”
mentioning
confidence: 99%
“…Moreover, local delivery of tTF-TMD through the skin barrier has been demonstrated (36,37). It is also notable that skin-penetrating capability of tRORγt-TMD and tTbet-TMD enables its therapeutic potency to be confined to local lesion area without systemic toxicity in a case of RA or in many skin autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%